Never - Follett, Ken (New York : Viking, 2021)
"A shrinking oasis in the Sahara Desert; a stolen US Army drone; an uninhabited Japanese island; and one country s secret stash of deadly chemical poisons: all these play roles in a relentlessly escalating crisis."--
Keywords: Deserts -- Fiction; Intelligence officers -- Fiction; Presidents -- United States -- Fiction; Women presidents -- Fiction; World politics -- Fiction; Spy fiction; Political fiction; Thrillers (Fiction)